Endemicity of avian influenza in ducks living around commercial layer farms - Simson Tarigan; Risa Indriani; . Sumarningsih (Indonesian Center for Animal Research and Development (ICARD), 2015)
The progenitors of all avian influenza viruses are generally derived from ducks or other waterfowl that have undergone mutation and adaptation to become pathogenic in chickens or other poultry. Investigation of the presence of avian influenza viruses in ducks especially those living around chicken farms is, therefore, important. Serum from 54 ducks and 51 Muscovy ducks living around commercial layer farms in the districts of Cianjur and Sukabumi were collected in March - April 2014. The indication of AI-virus infection in those birds was based on an array of serological tests including competitive and indirect ELISAs for antibody to nucleoprotein, MM2e ELISA for antibody to M2e, HI test, ELISAs and dot blot for antibodies to haemagglutinin, and dot blot assay for antibodies to neuraminidase. Recombinant Haemagglutinins (H1-H13 and H15), recombinant neuraminidases (N1, N2, N7 and N9) and recombinant influenza-A nucleoprotein were used in the indirect ELISAs and dot blot assays. As many as 63% of duck samples and 13% Muscovy-duck samples were serologically positive to nucleoprotein, and 62% of the nucleoprotein-seropositive ducks were also positive to M2e. The high seroprevalence of AI in the ducks living around commercial poultry farms suggested that application of strict biosecurity measures on those farms is still needed. Based on the results of the ELISA and dot blot assays, AI virus subtypes H9N2 and H5N2, in addition to H5N1, were suspected to be circulating in those ducks. Further confirmation by virus isolation, however, is required because H9N2 and H5N2 subtypes have yet been unknown Indonesia and both the subtypes can cause serious disease in poultry.Key Words: Duck, Immunoassay, Avian Influenza, H5N1, H5N2, H9N2